Case Report: CAR-T cell therapy bridging to allogeneic hematopoietic stem cell transplantation triggers Purtscher-like retinopathy: clinical features and complement-mediated microvascular injury mechanisms - Li, Zhihui; Zhang, Tao; Fei, Qian; Wang, Xianxuan; Li, Jing; Tao, Yong; Wu, Tong (Frontiers in Immunology, 2026)
Purtscher-like retinopathy (PLR) is a secondary, non-traumatic occlusive microvascular retinal disease characterized by retinal leukoderma, hemorrhage, and cotton wool spots. It is commonly associated with conditions such as pancreatitis, renal disease, and infections including COVID-19 but is rarely reported in patients with hematologic malignancies, particularly following hematopoietic stem cell transplantation (HSCT). This article reports a case of relapsed B-cell acute lymphoblastic leukemia (B-ALL) in a patient who underwent multiple lines of immunotherapy, including CD19- and CD22-targeted CAR-T cells, inotuzumab ozogamicin (an anti-CD22 antibody–drug conjugate), and belimumab (a CD19/CD3 bispecific T-cell engager), followed by allogeneic HSCT from an unrelated donor. Early post-transplantation, an influenza A (H1N1) infection likely triggered the onset of PLR. On post-transplant day 160, the patient presented with sudden, painless vision loss in the left eye. Fundoscopic examination revealed retinal hemorrhages, Purtscher flecken, and macular edema, confirming the diagnosis of PLR. By day 194, new-onset thrombocytopenia, proteinuria, and progressively elevated serum creatinine levels suggested an association between PLR and transplant-associated thrombotic microangiopathy (TA-TMA). This case illustrates that multi-agent immunotherapy prior to HSCT for acute leukemia may cause cumulative endothelial injury and that influenza A infection can act as a trigger for PLR in the post-HSCT setting. Early recognition and management of PLR and TA-TMA could improve clinical outcomes. Consequently, close monitoring for these complications is essential in post-transplant patients, particularly those with a history of intensive immunotherapy or subsequent viral infection. Implementing a “systemic-local” endothelial monitoring framework may facilitate timely intervention and enhance patient prognosis.